PUNISHMENT IN ISLAMIC EDUCATION FROM THE PROPHET'S HADITH PERSPECTIVE - Faizal Lubis (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
Punishment is an instrument in the educational process that aims to foster discipline, improve behavior, and instill responsibility in students. From an Islamic educational perspective, punishment is not the primary goal, but rather a last resort after efforts to advise, model, habituate, and guide fail to produce the desired change. This study aims to analyze the concept of punishment in Islamic education based on the hadith of the Prophet Muhammad (peace be upon him), specifically the hadith narrated by Abu Dawud concerning the command to teach prayer to children from the age of seven and the imposition of punishment at the age of ten for those who neglect it. This study uses a qualitative approach with a library research method through analysis of the hadith, Islamic educational literature, and the views of scholars on the concept of punishment. The results of the study indicate that Islam permits the imposition of punishment as a means of education provided that it is educational, proportional, not driven by emotion, does not cause physical or psychological harm, and is carried out after an adequate process of guidance and habituation. The Prophet's hadith emphasizes that punishment must be preceded by a continuous educational process over several years, so that its primary purpose is to develop students' awareness, discipline, and morals, not as a form of retribution. Thus, the concept of punishment in Islamic education emphasizes a balance between compassion, appreciation, and firmness in order to foster the character development of students who are faithful, have noble morals, and are responsible.